MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN KELAS VIII-2 SMP NEGERI 4 TEBING TINGGI - Mangatur Marpaung (FIP Unimed, 2017)
This study aims to determine the use of experimental methods in improving students' learning activeness in science lessons in class VIII-2 SMP Negeri 4 Tebing Tinggi. The subjects of the study were students of class VIII-2, amounting to 35 people. The result of research on student learning activity in the first cycle of meeting I is 71,52% (active enough), cycle I second II that is 72,30% (active enough), in cycle II meeting I that is 82,30% (active), cycle II meeting II is 84.01% (active). The result of observation of classroom teacher about the implementation of experimental method of cycle I meeting I is 68,75% (less good), cycle I meeting II is 78,12% (good enough), in cycle II meeting I is 87,5% (good) Cycle II meeting II is 93,75% (very good). Keywords: Learning Activeness, Experimental Methods, IPA